Adhésion médicamenteuse chez les coronariens âgés: expérience marocaine - Nouamou, Imad (Pan Afr Med J, 2019)
The treatment of coronary artery diseases has made significant progress. Medication adherence among patients with coronary artery disease, in particular among elderly patients, is a major challenge to disease control and prevention of its complications. Medication adherence could be influenced by the demographic and socio-economic vulnerable situation in the African countries. We conducted a cross-sectional study of elderly patients treated for stable coronary artery disease on an ambulatory basis from March to October 2016. Medication adherence was evaluated by a questionnaire: Morisky Medication Adherence Scale. The informations about predictive factors of medication adherence were obtained from a multidimensional adherence model. The study involved 115 elderly patients (age > 65 years). Medication adherence accounted for 72.2%, according to Morisky Medication Adherence Scale. Physical inactivity was found in 59% of patients, hypertension and diabetes in 42.6% and 41.7% of patients respectively. Poor compliance predictive factors were: the absence of a mutual health (p = 0.02), the severity of symptoms (p = 0.001), patients who had acute coronary syndrome (p = 0.006), the level of social support (p = 0.011) and depression (p = 0.006). Medication adherence is a health problem in Morocco, particularly among elderly subjects. Health care providers should be aware of factors associated with a higher probability of stopping treatment, in particular of variable factors, in order to implement personalized strategies to improve adherence to treatment.